Vertical dynamic interaction factors for offshore thin-walled pipe piles. (May 2022) - He, Rui; Zhang, Jisheng; Zheng, Jinhai
Abstract: With the development of offshore wind power in deep water, jacket foundations are increasingly used. These piles are always thin-walled pipe piles, whose dynamic interactions are different from onshore pile groups in several ways; for example, scour may develop around the piles, which may reduce a single pile's impedance, the dynamic interactions between piles and the impedances of pile groups. Jacket foundations are usually exposed to marine dynamic loads and are likely to experience vertical and rocking vibrations. Both kinds of vibrations are related to the vertical dynamic interaction between piles, which are the focus of this study. The effects of soil rigidity, soil permeability, pile spacing, excitation frequency, scour type and scour depth on dynamic vertical interaction factors are studied in this paper by a rigorous semi-analytical method. Numerical results for parameter analysis are illustrated, and corresponding simplified closed-form equations to predict dynamic interactions are also deduced. The dynamic interaction factors are then used to study tripod piles and tetrapod piles. Dynamic interaction may increase or decrease the pile impedances, mostly depending on the pile spacing ratio and non-dimensional frequency, and closed-form equations are obtained to forecast the amplification or reduction.